The Higher Level of Neutrophil – Lymphocyte Ratio (NLR) and Serum Syndecan-1 Based on Timeline (First, Sixth, and Twenty-Fourth Hour) in Sepsis-Induced Acute Kidney Injury - Lila Tri Harjana; Eddy Rahardjo; Windhu Purnomo; Lilik Herawati; Nancy Margarita Rehatta (Institute of Medico-legal Publications Pvt Ltd, 2022)
This study aims to analyze the difference between the NLR and serum syndecan-1 level at the first,sixth, and twenty-fourth hours with the incidence of acute kidney injury (AKI) and non-AKI in sepsis.We observed thirty-one adult sepsis patients who admitted to the emergency room and ICU of Dr.Soetomo General Academic Hospital, Surabaya, Indonesia from March 30, 2020, to July 5, 2020 (fourmonth),and differentiated into two groups, AKI group (n=14) and non-AKI group (n=17). All septicpatients have been given the standard treatment based on Survival Sepsis Campaign 2018. The resultsshowed that the NLR at 1st-hours, 6th-hours, and 24th-hours in the non-AKI group were lower thanthose in the AKI group (1st: 15.9±2.6 vs 33.0±11.3; 6th: 14.2±1.8 vs 19.3±3.8; and 24th: 11.6±1.3 vs19.9±3.8) (p <0.00). Almost NLR at every groups based on serial hours were decreasing, except in theAKI group, the NLR at the 24th-hour group was higher than the NLR at 6-hour group, but still lowerthan the NLR at 1st-hours. Serum syndecan-1 levels were lower in the non-AKI group than in theAKI group, at 1st, 6th, and 24th-hours, (1st: 532.5±72.0 ng/mL vs 597.2±85.8 ng/mL; 6th: 557.6±71.6ng/mL vs 612.0±73.9 ng/mL; and 24th: 548.4±76.6 ng/mL vs 586.4±84.6 ng/mL) (p <0.05). It canbe concluded that the neutrophil-lymphocyte ratio (NLR) and serum syndecan-1 levels at 1st, 6th,and 24th hours is higher in the AKI compared to non-AKI groups in sepsis. Hence, NLR and serumsyndecan-1 have a potential biomarkers for sepsis-induced AKI.